Communication Space of the Northern Pontic Area as Viewd by Aegeans - Suchowska, Paulina (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2009)
As regards the identification of the early forms of Europe's long-distance routes, the area lying between the Baltic and Black seas can be said to be one of relative neglect. Specifically, little research has been devoted to the development stages of the area's socio-cultural map, i.e. to neighbourly forays, itineraries, routes (of varied continuity, range and transport technique), stable segments of roads leading to water crossings, networks of fords and the communication channels running along watersheds. The foremost issue, at present one of great difficulty with respect to a study embracing the whole region in question, is the cultural context of these innovations and the related mechanisms that saw their creation in regard to the socio-economic basis and ritual-epistemological nature of ancient peoples in these regions. The study by Marija Gimbutas [Gimbutas 1965] of 'amber routes', joining the west and east of Europe, may be considered the first attempt to tackle the issue of the region's early communication channels and was accordingly referred to in the analyses of the distribution of stone 'fluted maces', regarded as hypothetical markers of Baltic-Pontic routes [Kośko 2001; 2002]. Generally, this conceptual leaven can be said to have provided broader intellectual stimuli for the international academic community of 'Archaeology Bimaris'. The turning point in the nascent study of ancient routes has been thus given a clear framework: an inter-university and interdisciplinary discussion (see the Poznań-Obrzycko symposium Routes Between the Seas: Baltic-Bug-Boh (Southern Bug)-Pont held in October 2008). The papers included in this volume are a partial record of the discussion. The intentional selectiveness here is seen therefore in the conscious limitation of the scope of papers ('piecemeal' treatment of linguistic or ethnological and anthropological analyses). Moreover, there is a special focus on one of the inter-regional routes, namely the Baltic-Bug-Boh (Southern Bug)-Pont, or more specifically, its early evidence (generally speaking, prior to - widely known to the academia - its use in the times of Goth migrations).